Imported Case of Lassa Fever in Sweden With Encephalopathy and Sensorineural Hearing Deficit. (20th September 2016) - Grahn, Anna; Bråve, Andreas; Lagging, Martin; Dotevall, Leif; Ekqvist, David; Hammarström, Helena; Karlberg, Helen; Lagerqvist, Nina; Sansone, Martina; Tegnell, Anders; Ulleryd, Peter; Studahl, Marie
Abstract: We describe an imported case of Lassa fever with both encephalopathy and bilateral sensorineural hearing deficit. Absence of fever during hospitalization, initially nonspecific symptoms, and onset of hearing deficit in a late stage of disease probably contributed to delayed diagnosis (14 days after admittance to hospital). The pathogenesis of neurological manifestations of Lassa fever is poorly understood and no specific treatment was given. A total of 118 personnel had close contact with the patient, but no secondary cases occurred. This case highlights the importance of considering Lassa fever as a differential diagnosis in patients with recent travel to endemic areas.